Sharia Economic Literacy in Preventing Generation Z’s Involvement in Online Gambling - Hamdan Ardiansyah; Vira Alisa Puspasari; Fathi Hafida Khoiriyah; Iqbal Wiyogo; Dini Agnia (Al-Sharf: Jurnal Ekonomi Islam, 2026)
The rapid advancement of digital technology has facilitated digital access, including to online gambling (maysir) among Generation Z, which triggers serious financial and psychological risks. The main problem is the low Sharia financial literacy index in Indonesia, which has only reached 39.11%. This makes Generation Z vulnerable to in-depth financial decision-making. This study aims to analyze the role of Sharia economic literacy as a preventative tool for Generation Z in dealing with the temptation of online gambling. The research method used was qualitative, descriptive, and analytical library research through a systematic literature search. The results indicate that a deep understanding of Sharia principles, such as the prohibition of usury, gharar, and maysir, can foster ethical and logical financial thinking, aimed at reducing interest in gambling among Generation Z. The study’s conclusions confirm that sharia literacy plays a crucial role as a preventative measure when integrated with moral strengthening and social environmental monitoring. The implication of this research are the need to strengthen a structured Sharia financial education curriculum and utilize monitoring technology to protect Generation Z from digital financial crime.